2005
DOI: 10.1007/s11267-005-0726-z
|View full text |Cite
|
Sign up to set email alerts
|

What Anthropogenic Radionuclides (90Sr and 137Cs in Atmospheric Deposition, Surface Soils and Aeolian Dusts Suggest for Dust Transport over Japan

Abstract: Currently, atmospheric anthropogenic radionuclides (particulate) are controlled by suspension of the surface dust containing those radionuclides (resuspension). We have found, therefore, that such radionuclides can be used as tracers of the surface dust suspension, transport and its subsequent deposition in distant areas. The 137 Cs/ 90 Sr activity ratios in the atmospheric deposition, without the direct influence of nuclear tests and accidents, at the Meteorological Research Institute (MRI, Tsukuba, Japan) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…In general, water-soluble cesium ions from SO 4 2− are considered to be adsorbed or attached to mineral particles in a soil environment (Bostic et al 2002;Dumat and Staunton 1999;Mukai et al 2014). These mineral particles were shown to act as resuspended host particles in an atmospheric environment by the previous investigations of the global fallout from atmospheric nuclear weapon tests (e.g., Igarashi et al 2005;Masson et al 2010). Therefore, a major resuspension source has been thought to be the suspension of contaminated dust particles by wind Ishizuka et al 2017;Sýkora et al 2012), even for the case of the FDNPP accident contamination.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In general, water-soluble cesium ions from SO 4 2− are considered to be adsorbed or attached to mineral particles in a soil environment (Bostic et al 2002;Dumat and Staunton 1999;Mukai et al 2014). These mineral particles were shown to act as resuspended host particles in an atmospheric environment by the previous investigations of the global fallout from atmospheric nuclear weapon tests (e.g., Igarashi et al 2005;Masson et al 2010). Therefore, a major resuspension source has been thought to be the suspension of contaminated dust particles by wind Ishizuka et al 2017;Sýkora et al 2012), even for the case of the FDNPP accident contamination.…”
Section: Introductionmentioning
confidence: 92%
“…Many studies have indicated that 137 Cs is firmly adsorbed to clay mineral particles (e.g., Dumat and Staunton 1999;Igarashi et al 2005;Masson et al 2010;Mukai et al 2014;Ishizuka et al 2017), and the transport of mineral dust particles by wind is considered to be a significant resuspension process. As shown in Fig.…”
Section: Possible Host Particles For Radiocesium Resuspensionmentioning
confidence: 99%
“…The 90 Sr and 137 Cs specific activities and the 137 Cs/ 90 Sr ratio of the Mongolian soil are summarized in Table 1 together with previously published values for surface soil and atmospheric total (wet + dry) deposition (Igarashi et al, 2005(Igarashi et al, , 2009. The data were decay-corrected as of fall 2007, the time the soil samples were collected in Mongolia.…”
Section: Sr and 137 Cs In Mongolian Surface Soilmentioning
confidence: 99%
“…137 Cs contamination detected in France during a Saharan dust event was suspected to be the result of leakage from past nuclear test sites in French Saharan territory (Danesi et al, 2008). Igarashi et al (2005) pointed out that close-in fallout from atmospheric nuclear explosions should have been an insignificant source of surface contamination of 90 Sr and 137 Cs around the test sites, thus negligible in aeolian dust transport; and French researchers drew similar conclusions (Menut et al, 2009;Masson et al, 2010). Only 0.7 % of the Saharan dust was ascribed to the test area, accounting for only a small percentage of the atmospheric 137 Cs peak concentrations recorded in France during the transport event (Menut et al, 2009).…”
Section: Appendix a A1 No Direct Link To Past Nuclear Testsmentioning
confidence: 99%
See 1 more Smart Citation